Wag the dog: a study on film and reality in the digital age (2015)
Wag the Dog is a good example to test Oscar Wilde’s claim. Directed by Barry Levinson and released in the theatres a few weeks before the outbreak of the Monica Lewinsky scandal in the press, the film appeared to prove the Irish wit right. The real life occurrences, namely President Clinton’s sexual affair with a White House intern and his subsequent attacks against foreign distant targets, seemed outright inspired by the movie plot. Yet, things are not quite that simple. In fact, this entire monograph is dedicated to exploring the complex relation between art and life, or rather cinema and reality, in order to do justice to the fine nuances of their intrinsic ties. These ties have occupied critics and scholars ever since the cinematic medium made its first steps in the beginning of the twentieth century. The result was a number of theoretical observations and philosophical positions regarding the ways in which cinema relates to the real world. In my own take here, I would like to scale down the size of the investi- gation and make a bottom-up start. By focusing on a single film and performing a meticulous analysis with a variety of tools and concepts, I would like to explore the details of the cinema/reality binary as it unfolds in the case of Wag the Dog. From the filmic texture and the story that it contains to the historical context and the conditions in which it was produced, exhibited and received worldwide, Wag the Dog constitutes an intriguing case in world film history that illuminates a series of operations in the way a fiction film interacts with reality. As we construe this interaction on multiple levels, we will be given the chance to assess a significant number of ideas and concepts from film theory and we will be faced with a number of questions as to how they could be reformulated vis-à-vis the contemporary cinematic experience.